Microsatellite alteration in multiple primary lung cancer - Shen, Cheng; Wang, Xin; Tian, Long; Che, Guowei (Journal of Thoracic Disease, 2014)
Patients with pulmonary neoplasms have an increased risk for developing a second tumor of the lung, either at the same time or different times. It is important to determine if the second tumor represents an independent primary tumor or recurrence/metastasis, because it will significantly change the management and prognosis. Microsatellite instability (MSI) and loss of heterozygosity (LOH) represents molecular disorders acquired by the cell during neoplastic transformation. Both are associated with genetic instability. Functional silencing of tumour suppressor genes may be the consequence of genomic instability, particularly of the globally occurring LOH phenomenon. Numerous studies have confirmed the role of MSI/LOH at both the early and the late stages of multiple primary lung cancer. This paper reviews the published literatures focused on the role of MSI/LOH significance in multiple primary lung cancer. Additionally, a new method based on the allelic variations at polymorphic microsatellite markers was offered that it does not rely on collection of normal tissue, performed with minimal tumor sample, and will complement clinical criteria for diagnostic discrimination between multiple primary cancers versus solitary metastatic diseases.